Stopping by the Woods: Classic American Poems in Yiddish - Waldinger, Albert (TTR)

(untitled) (Association canadienne de traductologie, 2003)
AbstractThis essay interprets and analyzes in detail the Yiddish versions of great American poems: Poe's "The Raven," Longfellow's "Hiawatha," Whitman's "Song of Myself" and Frost's "Stopping by Woods on a Snowy Evening." An attempt has been made to relate all cross-linguistic data to cultural and social ideologies like Poetic Professionalism, Americanization, Socialism, Preservation of Ethnic Identity and Personal/Communal Expressiveness. In other words, the main intent of the essay has been to "explicate" a text by reference to its cultural context, whether American or Jewish.